Eksplorasi Serat Kapuk Dengan Pewarna Kulit Ubi Ungu dan Teknik Felting - Nurrika Chandra; Yunita Fitra Andriana; Dedy Rachmad Setiawardhana (Fakultas Teknik Universitas Persada Indonesia YAI, 2022)
The kapok tree or commonly called the randu kapok tree, is a multifunctional plant that is easilyfound in Indonesia. In the industrial world, kapok is most widely used for stuffing pillows,mattresses and other objects to increase volume. But nowadays kapok is rarely in demand becausepeople prefer mattress products with foam and spring base materials. So far, kapok processing hasnot been optimal, with this research it is hoped that kapok can be a material that is on the surfaceof objects, no longer just as a filling. The series of exploration processes in this study used naturalpurple sweet potato skin dye and felting technique. The results of the exploration are expected tooptimize the visual character of kapok fiber so that it has aesthetic value